Immunogenicity, safety, and tolerability of the measles-vectored chikungunya virus vaccine MV-CHIK: a double-blind, randomised, placebo-controlled and active-controlled phase 2 trial. Issue 10165 (22nd December 2018) - Reisinger, Emil C; Tschismarov, Roland; Beubler, Eckhard; Wiedermann, Ursula; Firbas, Christa; Loebermann, Micha; Pfeiffer, Andrea; Muellner, Matthias; Tauber, Erich; Ramsauer, Katrin
Summary: Background: Chikungunya fever is an emerging viral disease and substantial threat to public health. We aimed to assess the safety, tolerability, and immunogenicity of a live-attenuated, measles-vectored chikungunya vaccine (MV-CHIK). Methods: In this double-blind, randomised, placebo-controlled and active-controlled phase 2 trial, we enrolled healthy volunteers aged 18–55 years at four study sites in Austria and Germany. Participants were randomly assigned to receive intramuscular injections with MV-CHIK (5 × 10 4 or 5 × 10 5 50% tissue culture infectious dose), control vaccine, or measles prime and MV-CHIK, in two different administration regimens. Randomisation was done by use of three-digit randomisation codes in envelopes provided by a data management service. The participants and investigators were masked to treatment assignment, which was maintained by use of sterile saline as a placebo injection. The primary endpoint was immunogenicity, defined as the presence of neutralising antibodies against chikungunya virus, at day 56, which is 28 days after one or two immunisations. The primary endpoint was assessed in all participants who completed the study without major protocol deviations (per-protocol population) and in all randomised participants who received at least one study treatment (modified intention-to-treat population). The safety analysis included all participants who received at least one study treatment. This trial is registered withClinicalTrials.gov (NCT02861586 ) and EudraCT (2015-004037-26) and is completed. Findings: Between Aug 17, 2016, and May 31, 2017, we randomly assigned 263 participants to receive control vaccine (n=34), MV-CHIK (n=195), or measles prime and MV-CHIK (n=34). 247 participants were included in the per-protocol population. Neutralising antibodies against chikungunya virus were detected in all MV-CHIK treatment groups after one or two immunisations, with geometric mean titres ranging from 12·87 (95% CI 8·75–18·93) to 174·80 (119·10–256·50) and seroconversion rates ranging from 50·0% to 95·9% depending on the dose and administration schedule. Adverse events were similar between groups, with solicited adverse events reported in 168 (73%) of 229 participants assigned to MV-CHIK and 24 (71%) of 34 assigned to control vaccine (p=0·84) and unsolicited adverse events in 116 (51%) participants assigned to MV-CHIK and 17 (50%) assigned to control vaccine (p=1·00). No serious adverse events related to the vaccine were reported. Interpretation: MV-CHIK showed excellent safety and tolerability and good immunogenicity, independent of pre-existing immunity against the vector. MV-CHIK is a promising candidate vaccine for the prevention of chikungunya fever, an emerging disease of global concern. Funding: Themis.